Aktivitas Kitinase dan Peroksidase dari Ekstrak Protein Daun, Akar, Kalus dan Tunas In Vitro Trichosanthes tricuspidata Lour. - Dewi Sukma; Roedhy Poerwanto; , Sudarsono; Nurul Khumaida; Suryo Wiyono; I Made Artika (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
A number of Trichosanthes species has been reported as a source of bioactive protein associated with defense mechanisms such as chitinase. Chitinase and peroxidase of crude protein extracted from leaves, roots, in vitro calli and shoots of T. tricuspidata had been analysed. Calli were induced on MS medium containing combinations of 1 µM NAA + 1 µM BA (K1), 2 µM NAA + 2 µM BA (K2), 3 µM NAA + 3 µM BA (K3), or 4 µM NAA + 4 µM BA (K4). Shoots were cultured in MS with 1 mg/l of BA, while leaves and roots were harvested from six-month old plants grown on the field. Results of the experiment suggested that K1-K4 medium could be used to induce calli although weight of calli from all medium composition was not significantly different (0.19-0.31 g/explant/4 weeks). Calli from K1 medium had the highest of total crude protein content (3.24 mg/ml). The highest of chitinase activity was found in in vitro shoots (6.51 mM pNP/hour/mg protein) and the highest peroxidase activity was in the plant roots (0.25 ∆ 420/minute/mg protein). Key words: in vitro calli, shoots, crude protein, chitinase and peroxidase activities